ANALISIS PENGARUH CAPITAL ADEQUACY RASIO (CAR) TERHADAP LABA BADAN USAHA MILIK DESA (BUMDES) (Studi Pada Bumdes Desa Jorok Kecamatan Unter Iwes) - I Nyoman Sutama; Binar Dwiyanto Pamungkas; Monita Nasrianti (Fakultas Ekonomi dan Manajemen, 2021)
The purpose of this study was to know the Effect of Capital Adequacy Ratio (CAR) toward Profit of Village Owned Enterprises (BUMDes) Jorok Village, Untir Iwes Sub-District, Sumbawa District in 2017 – 2020. The type of this study was associative. The source of data used in this study was secondary data obtained from Bumdes Financial Report relating to Assets, Capital and Income of BUMDes in Jorok Village, Untir Iwes Sub-District, 2017-2020. Methods used to collect data were through documentation and literature study. The analytical method used was simple linear regression method. Results of study showed that Capital Adequate Ratio (CAR) did not have effect toward profit of Village Owned Enterprise (BUMDes) of Jorok Village, Unter Iwes Sub-District, Sumbawa District in 2017 – 2020, it was based the t-value was lower than t-table (-1.084 < 2.920) with a significance value of 0.001. The value of coefficient of determination was 0.370 or 37.0 percent. It means that the percentage effect of capital adequate ratio toward profit of BUMDes of Jorok Village Unter Iwes Sub-district in 2017-2020 was 37% while the remaining of 63% was caused by other variables outside the scope of the study.